Which Model Better Fits the Role of Aire in the Establishment of Self-Tolerance: The Transcription Model or the Maturation Model? - Matsumoto, Mitsuru (Frontiers in Immunology, 2013)
The discovery of Aire-dependent transcriptional control of many tissue-restricted self-antigen (TRA) genes in thymic epithelial cells in the medulla (mTECs) has raised the intriguing question of how the single Aire gene can influence the transcription of such a large number of TRA genes within mTECs. From a mechanistic viewpoint, there are two possible models to explain the function of Aire in this action. In the first model, TRAs are considered to be the direct target genes of Aire’s transcriptional activity. In this scenario, the lack of Aire protein within cells would result in the defective TRA gene expression, while the maturation program of mTECs would be unaffected in principle. The second model hypothesizes that Aire is necessary for the maturation program of mTECs. In this case, we assume that the mTEC compartment does not mature normally in the absence of Aire. If acquisition of the properties of TRA gene expression depends on the maturation status of mTECs, a defect of such an Aire-dependent maturation program in Aire-deficient mTECs can also result in impaired TRA gene expression. In this brief review, we will focus on these two contrasting models for the roles of Aire in controlling the expression of TRAs within mTECs